DETALLES MORFOLOGICOS DE LOS ANOPHELES AMERICANOS DEL GRUPO MACULIPENNIS Y ESPECIES PROXIMAS - VARGAS, LUIS (My University, 1941)
The American spp which form part of the maculipennis group of the Old World are A aztecus, A freeborni, and A occidentalis, frequently considered as vars A key of morph characters is given which permits the identification of these spp and the clos
CIENC MEX
Keywords: MORFOLOGICOS, ANOPHELES, AMERICANOS, MACULIPENNIS ESPECIES; CIENCIAS MEDICAS; PATOLOGIA; PATOLOGIA EXPERIMENTAL